Enhancing Syntactic Complexity in L2 Chinese Writing: Effects of Form-Focused Instruction on the Chinese Topic Chain - Zhou, Jieyu; Lü, Chan (Frontiers in Psychology, 2022)
Syntactic complexity, as one aspect of the Complexity, Accuracy and Fluency (CAF) model, is integral to the writing ability of second language (L2) learners. Previous research found that T-unit-based measures of syntactic complexity in writing tasks of English as a Second Language (ESL) learners increased with more instruction, yet it remains unclear whether the same can be observed in Chinese as a second language (CSL) learners. To fill this gap, this study compared the development of syntactic complexity of a training group (N=64) and a control group (N=51), both composed of CSL students in a first-year Chinese course at a university in North America. While participants in the control group only participated in the regular course, the training group received an additional 10-week, explicit form-focused instruction (FFI) on the Chinese topic chain. Results on the posttest and delayed posttest show that the FFI on the topic chain had a positive and durable effect on the participants’ syntactic complexity; instructional intensity and feedback type may have influenced its effectiveness and durability. Characteristics of measures and task complexity may have affected the observation of syntactic complexity.